The Joint Determination of Leverage and Maturity: Empirical Evidence from Malaysia - Aprilia, Rini (2012)
This study empirically investigates the simultaneity between leverage and debt maturity policies and the factors that influence them by using a simultaneous equations framework in which leverage and debt maturity are endogenous variables. Based on a panel data of 788 non-financial firms listed on Bursa Malaysia from 1999 until 2010, this study estimates a single equation model on leverage and debt maturity using an Estimated Generalized Least Squares (EGLS) approach. The simultaneity between leverage and debt maturity is tested by utilizing a two-stage least squares(2SLS) regression model. The results of this study show that leverage and debt maturity policies have a negative simultaneous relationship which indicates that there are strategic complementarities between leverage and maturity. This study also documents different results among the exogenous variables in both equations, in which growth opportunities, regulation, firm size, profitability and tangibility lend considerable support to the proposed hypotheses on the leverage equation. Meanwhile, firm size, regulation, abnormal earnings and tangibility are found to have significant effects on the debt maturity equation.